ILLOCUTIONARY ACTS FOUND IN THE NOVEL THE LAST LEAVES FALLING BY SARAH BENWELL (Sastra Inggris UNPAM, 2022)
This study aims to classify and explain the functions of illocutionary act used in the novel entitled The Last Leaves Falling by Sarah Benwell. After being collected, the data is analyzed based on the theory of illocutionary act by George Yule (1996). The object of this study is the novel itself. This study uses a qualitative method with descriptive analysis. Based on the result, there are 68 items found in the novel, there are 21 directives, with the function such as suggesting, commanding, and requesting, 16 representatives, with the function such as stating, concluding, and describing, 16 expressive, with the function such as a statement of joy, anger, like, dislike, 8 commissive, with the function such as promising and refusing and 7 declarations, with the function declaring. The most dominant type of illocutionary act that is found is directives with 21 items or 30,88%, while the least type is declaration with 7 items or 10,29%. The directive act became the most dominant act in the last leaves falling novel due the main character is a teen who was diagnosed with Amyotrophic Lateral Sclerosis. Keywords: Pragmatics, Speech act, Illocutionary acts, Qualitative method.